Integrated network pharmacology and molecular docking analysis of Aerva sanguinolenta n-hexane extract against breast cancer - Harahap, Armansyah Maulana; Agustini, Kurnia; Ningsih, Sri; Bahtiar, Anton (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Breast cancer, particularly the estrogen receptor-positive (ER-positive) subtype, remains a significant global health challenge. Although Aerva sanguinolenta (AS) has shown Anti-cancer potential, its comprehensive mechanistic effects on breast cancer are still largely unknown. This study aims to uncover the pharmacological effects of AS bioactive compounds on breast cancer using an integrated network pharmacology and molecular docking approach. Bioactive compounds in AS were identified through GC-MS. Compound-target and breast cancer gene interactions were obtained from various databases, followed by protein-protein interaction, Gene Ontology, and KEGG pathway analyses. Molecular docking studies were then used to confirm key interactions. We found that 4 of 103 AS compounds met strict screening criteria, identifying 712 potential gene targets, 33 of which were directly related to breast cancer, including hormonal (ESR1) and apoptosis (AURKA) pathways. Further analysis and molecular docking confirmed the strong binding affinity of Bakuchiol and Afzelin compounds to their main targets, which are involved in critical biological processes such as estrogen receptor signaling, cell cycle regulation, and pathways related to cell proliferation and breast cancer development. In conclusion, this study provides a comprehensive understanding of the potential mechanisms of AS bioactive compounds Afzelin and Bakuchiol against breast cancer, demonstrating their therapeutic potential through Network Pharmacology and docking scores.